Gene Expression Signature of Traumatic Brain Injury - Ma, Yawen; Liu, Yunhui; Ruan, Xuelei; Liu, Xiaobai; Zheng, Jian; Teng, Hao; Shao, Lianqi; Yang, Chunqing; Wang, Di; Xue, Yixue (Frontiers in Genetics, 2021)
Background Traumatic brain injury (TBI) is a brain function change caused by external forces, which is one of the main causes of death and disability worldwide. The aim of this study was to identify early diagnostic markers and potential therapeutic targets for TBI. Methods Differences between TBI and controls in GSE89866 and GSE104687 were analyzed. The two groups of differentially expressed genes (DEGs) were combined for co-expression analysis, and the modules of interest were performed enrichment analysis. Hub genes were identified by calculating area under curve (AUC) values of module genes, PPI network analysis and functional similarity. Finally, the difference in immune cell infiltration between TBI and control was calculated by ssGSEA. Results A total of 4817 DEGs were identified in GSE89866 and 1329 DEGs in GSE104687. They were clustered into nine modules. The genes of modules 1, 4 and 7 had the most cross talk and were identified as important modules. Enrichment analysis revealed that they were mainly associated with neurodevelopment, immune inflammation. In the PPI network constructed by genes with top 50 AUC values in module genes, we identified the top 10 genes with the greatest connectivity. Among them, down-regulated RPL27, RPS4X, RPL23A, RPS15A and RPL7A had similar functions were identified as hub genes. In addition, DC and Tem were significantly up-regulated and down-regulated between TBI and control, respectively. Conclusion We found that hub genes may have a diagnostic role for TBI. Molecular dysregulation mechanisms of TBI are associated with neurological and immune inflammation. These results may provide new ideas for the diagnosis and treatment of TBI.